Using computer-based tests for information science - David Callear; Terry King (Association for Learning Technology, 1997)
The introduction of objective testing using computer software does not necessarily represent innovative assessment. Where tests occur as an add-on to a course, are timeconstrained, closed-book, invigilated, and where there is little (or no) feedback of results to the students, such testing is best regarded as an innovative technique for traditional summative assessment. A computer-based examination of this nature using the commercial software Question Mark has been operating for a number of years in the Department of Information Science at Portsmouth, in the second-year unit for Logic Programming, with student numbers up to 160.